2005
DOI: 10.1117/12.619310
|View full text |Cite
|
Sign up to set email alerts
|

Modeling contamination migration on the Chandra X-ray Observatory

Abstract: During its first 6 years of operation, the cold (-60°C) optical blocking filter of the Advanced CCD Imaging Spectrometer (ACIS), on board the Chandra X-ray Observatory, has accumulated a contaminating layer that attenuates the low-energy x rays. To assist in assessing the likelihood of successfully baking off the contaminant, members of the Chandra team developed contamination-migration simulation software. The simulation follows deposition onto and (temperature-dependent) vaporization from surfaces comprising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The time evolution of the thickness of the Carbon contamination layer is well fitted with an exponential model [6]. The contamination on the EPIC detectors is, however, much lower than what found on Chandra and Suzaku [7,8].…”
mentioning
confidence: 99%
“…The time evolution of the thickness of the Carbon contamination layer is well fitted with an exponential model [6]. The contamination on the EPIC detectors is, however, much lower than what found on Chandra and Suzaku [7,8].…”
mentioning
confidence: 99%
“…Based upon previous experience and extensive ground testing, the ACIS Team and NGST concluded that a bake would be safe for the ACIS. In order to assess the effectiveness of a potential bake out, Project Science developed and utilized software to simulate molecular transport within the Observatory 49 , using a geometrical model developed by NGST (for thermal analysis) and temperatures provided by NGST and LMA (ACIS systems integrator). Because the identity of the primary contaminant remains unknown 50 and temperatures of some critical surfaces are uncertain, we had to simulate contamination migration for a range of volatilities and surface temperatures.…”
Section: Operationmentioning
confidence: 99%